Iron Status May Not Affect Amyotrophic Lateral Sclerosis: A Mendelian Randomization Study - Cai, Jiahao; Chen, Xiong; Wang, Hongxuan; Wei, Zixin; Li, Mei; Rong, Xiaoming; Li, Xiangpen; Peng, Ying (Frontiers in Genetics, 2021)
Background: Observational studies have shown an association of increased iron status with a higher risk of amyotrophic lateral sclerosis (ALS). Iron status might be a novel target for ALS prevention if a causal relationship exists. We aimed to reveal the causality between iron status and ALS incidence using a large two-sample Mendelian randomization (MR). Methods: Single nucleotide polymorphisms (SNPs) for iron status were identified from a genome-wide association study (GWAS) on 48,972 individuals. The outcome data came from the largest ALS GWAS to date (20,806 cases; 59,804 controls). We conducted conservative analyses (using SNPs with concordant change of biomarkers of iron status) and liberal analyses (using SNPs associated with at least one of the biomarkers of iron status), with inverse variance weighted (IVW) method as the main analysis. We then performed sensitivity analyses including Weighted median, MR-Egger and MR-pleiotropy residual sum and outlier, as well as leave-one-out analysis to detect pleiotropy. Results: In the conservative analyses, we found no evidence of association between 4 biomarkers of iron status and ALS using IVW method with odds ratio (OR) 1.00 (95% confidence interval [CI]: 0.90 - 1.11) per standard deviation (SD) increase in iron, 0.96 (95% CI: 0.77 - 1.21) in ferritin, 0.99 (95% CI: 0.92 - 1.07) in transferrin saturation and 1.04 (95% CI: 0.93 - 1.16) in transferrin. Findings from liberal analyses were similar and sensitivity analyses suggested no pleiotropy detected (all p > 0.05). Conclusion: Our findings suggest no causal effect between iron status and risk of ALS. Efforts to change the iron status to decrease ALS incidence might be impractical.